Creativity Model in Improving Organizational Performance at Hasanuddin University Hospital Makassar - Yusi Irensi Seppa; Muh. Rizal S; Siti Syarifah Wafiqah Wardah; Aris Baharuddin; Andi Muhammad Rivai (Jurnal Office, 2023)
Challenge human resources management is creating various organizations' variety but demands efficient, effective, and also productive knowledge. This study discusses the creativity model in improving organizational performance at Hasanuddin University Hospital Makassar. This hospital has facilities and human resources consisting of medical and non-medical personnel to support all service activities. However, the application of the right model of creativity in work has not been fully implemented properly. there are still employees who do not have creativity at work, especially in solving problems when working. To be able to improve organizational performance at the Hasanuddin University Makassar Hospital, an appropriate creativity model is needed that can be applied in facing increasingly fierce competition in the Industrial Revolution era which features technological excellence. This study aims to determine the creativity model for improving organizational performance at Hasanuddin University Hospital Makassar. The type of research used is descriptive qualitative research where this research describes in depth by examining all the problems that occur related to the research focus with a phenomenological approach. Data collection techniques in the form of Observation, Interview, and Documentation. Data analysis techniques include examining all available data that has been obtained from various sources, presenting data, and verifying it. The results of the study show that the creativity model in improving organizational performance has been implemented quite well, where most employees have enough creativity at work. For organizational performance to get better, the Hasanuddin University Makassar Hospital should always develop an appropriate and appropriate model of creativity.